Born and made : an ethnography of preimplantation genetic diagnosis - Franklin, Sarah, 1960- (In-formation series., 2006)
Are new reproductive and genetic technologies racing ahead of a society that is unable to establish limits to their use? Have the ""new genetics"" outpaced our ability to control their future applications? This book examines the case of preimplantation genetic diagnosis (PGD), the procedure used to prevent serious genetic disease by embryo selection, and the so-called ""designer baby"" method. Using detailed empirical evidence, the authors show that far from being a runaway technology, the regulation of PGD over the past fifteen years provides an example of precaution and restraint, as well